A microsimulation model to assess the economic impact of immunotherapy in non-small cell lung cancer. Issue 2 (19th April 2020) - Legoupil, Clémence; Debieuvre, Didier; Marabelle, Aurelien; Michiels, Stefan; Kapso, Raïssa; Besse, Benjamin; Bonastre, Julia
Introduction: Immunotherapy has become the standard of care in advanced non-small cell lung cancer (NSCLC). We aimed to quantify the economic impact, in France, of anti-PD-1 therapy for NSCLC. Methods: We used patient-level data from the national ESCAP-2011-CPHG cohort study to estimate time to treatment failure and mean cost per patient for the four label indications approved by the European Medicines Agency (EMA) for NSCLC in May 2018. To compute the budget impact, we used a microsimulation model to estimate the target populations of anti-PD-1 therapy over a 3-year period, which were combined with the annual cost of treatment. Results: Overall, 11 839 patients with NSCLC were estimated to be eligible for anti-PD-1 therapy 3 years after the introduction of anti-PD-1 therapies. The mean annual cost per patient in the control group ranged from €2671 (95% CI €2149–3194) to €6412 (95% CI €5920–6903) across the four indications. The mean annual cost of treatment for the four EMA-approved indications of anti-PD-1 therapy was estimated to be €48.7 million in the control group and at €421.8 million in the immunotherapy group. The overall budget impact in 2019 is expected to amount to €373.1 million. In the sensitivity analysis, flat doses and treatment effect had the greatest influence on the budget impact. Conclusion: Anti-PD-1 agents for NSCLC treatment are associated with a substantial economic burden. Anti-PD-1 agents for NSCLC treatment are associated with a substantial economic burden http://bit.ly/2SDXZw0